A System for Culturing Iris Pigment Epithelial Cells to Study Lens Regeneration in Newt - Bhavsar, Rital B. (MyJove Corporation, 2011)
Salamanders like newt and axolotl possess the ability to regenerate many of its lost body parts such as limbs, the tail with spinal cord, eye, brain, heart, the jaw (1). Specifically, newts are unique for its lens regeneration capability. Upon lens removal, IPE cells of the dorsal iris transdifferentiate to lens cells and eventually form a new lens in about a month (2,3). This property of regeneration is never exhibited by the ventral iris cells. The regeneration potential of the iris cells can be studied by making transplants of the in vitro cultured IPE cells. For the culture, the dorsal and ventral iris cells are first isolated from the eye and cultured separately for a time period of 2 weeks (Figure 1). These cultured cells are reaggregated and implanted back to the newt eye. Past studies have shown that the dorsal reaggregate maintains its lens forming capacity whereas the ventral aggregate does not form a lens, recapitulating, thus the in vivo process (Figure 2) (4,5). This system of determining regeneration potential of dorsal and ventral iris cells is very useful in studying the role of genes and proteins involved in lens regeneration.